Revisiting the dissolution of cellulose in H3PO4(aq) through cryo-TEM, PTssNMR and DWS. (15th January 2021) - Alves, Luís; Medronho, Bruno; Filipe, Alexandra; Romano, Anabela; Rasteiro, Maria G.; Lindman, Björn; Topgaard, Daniel; Davidovich, Irina; Talmon, Yeshayahu
Abstract: Cellulose can be dissolved in concentrated acidic aqueous solvents forming extremely viscous solutions, and, in some cases, liquid crystalline phases. In this work, the concentrated phosphoric acid aqueous solvent is revisited implementing a set of advanced techniques, such as cryo-transmission electronic microscopy (cryo-TEM), polarization transfer solid-state nuclear magnetic resonance (PTssNMR), and diffusing wave spectroscopy (DWS). Cryo-TEM images confirm that this solvent system is capable to efficiently dissolve cellulose. No cellulose particles, fibrils, or aggregates are visible. Conversely, PTssNMR revealed a dominant CP signal at 25 °C, characteristic of C-H bond reorientation with correlation time longer than 100 ns and/or order parameter above 0.5, which was ascribed to a transient gel-like network or an anisotropic liquid crystalline phase. Increasing the temperature leads to a gradual transition from CP to INEPT-dominant signal and a loss of birefringence in optical microscopy, suggesting an anisotropic-to-isotropic phase transition. Finally, an excellent agreement between optical microrheology and conventional mechanical rheometry was also obtained.